2009
DOI: 10.1074/jbc.m803792200
|View full text |Cite
|
Sign up to set email alerts
|

His-75 in Proteorhodopsin, a Novel Component in Light-driven Proton Translocation by Primary Pumps

Abstract: A variety of unicellular microorganisms contain primary proton pumps that convert solar energy into a transmembrane electrochemical proton gradient, which is subsequently used by membrane ATP synthases to generate chemical energy. Well known examples of such pumps are the haloarchaeal rhodopsins, photoactive, seven-helix membrane proteins, which include the well studied proton pump bacteriorhodopsin (BR) 4 from Halobacterium salinarum and BR homologs in other haloarchaea. Recently, a much larger new family of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
83
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 35 publications
8
83
0
Order By: Relevance
“…However, densitometry calculations (not shown) reveal that total protein incorporation efficiency in a pH 5 environment is markedly less compared with incorporation at pH 6.2. Previous studies have shown that pR becomes unstable at lower pH values and causes precipitation (28). At pH 9, however, the C-terminal effective charge becomes À3.8 and the N-terminal remains unchanged at À2.…”
Section: Limited Proteolysismentioning
confidence: 94%
“…However, densitometry calculations (not shown) reveal that total protein incorporation efficiency in a pH 5 environment is markedly less compared with incorporation at pH 6.2. Previous studies have shown that pR becomes unstable at lower pH values and causes precipitation (28). At pH 9, however, the C-terminal effective charge becomes À3.8 and the N-terminal remains unchanged at À2.…”
Section: Limited Proteolysismentioning
confidence: 94%
“…During the reaction, His 61 and Arg 92 are thought to be involved in the maintenance of both the pK a values of the charged residues and the proper structural changes of the peptide backbone analogous to the other eubacterial proton pumps including XR (18,(43)(44)(45)(46). Unfortunately, we cannot discuss the structural details of TR at the atomic level by precisely comparing them with XR or other microbial rhodopsins because of the present modest resolution (2.8 Å).…”
mentioning
confidence: 99%
“…Most importantly, the pK a of the primary proton acceptor Asp 97 is almost unaffected. Previous studies have shown that the protonation of Asp 97 in helix C is stabilized by an interaction with His 75 in helix B (23,35). In our case, helices B and C belong to two separately expressed fragments that are connected through the trans-splicing reaction.…”
mentioning
confidence: 98%